Long non‐coding RNA ROR promotes proliferation, migration and chemoresistance of nasopharyngeal carcinoma. Issue 9 (1st September 2016) - Li, Li; Gu, Miao; You, Bo; Shi, Si; Shan, Ying; Bao, Lili; You, Yiwen
Abstract : Nasopharyngeal carcinoma (NPC) is one of the most common malignancies of the head and neck. It arises from the nasopharynx epithelium and is associated with high morbidity and mortality. Long non‐coding RNA (lncRNA) have been reported to regulate gene interaction and play critical roles in carcinogenesis and progression. LncRNA‐ROR, a recently identified lncRNA, has been shown to be involved in initiation, progression and metastasis of several tumors, including hepatocellular carcinoma, breast cancer and glioma. However, whether lncRNA‐ROR is associated with the progression of NPC remains unknown. Resistance to radiotherapy and chemotherapy is the primary cause of NPC patients' death. In this study, we found that lncRNA‐ROR was significantly upregulated in NPC tissues compared with normal tissues. Next, our study proved that lncRNA‐ROR was highly associated with the proliferation, metastasis and apoptosis of NPC. The enrichment of lncRNA‐ROR played a critucal functional role in chemoresistance. The mechanism by which NPC resists chemotherapy might be that lncRNA‐ROR suppress p53 signal pathway. Taken together, these data suggested that lncRNA‐ROR played an important role in the progression of NPC; thereby it might become a therapeutic target and reduce chemoresistance for NPC. Abstract : lncRNA‐ROR was upregulated in NPC tissues compared with normal tissues and it was highly associated with NPC proliferation, metastasis and apoptosis. The most important thing is that the enrichment of lncRNA ROR played a crucial functional role in chemoresistance. The mechanism might be that lncRNA ROR suppress p53 signal pathway to resist chemotherapy.